Let's solve the logarithmic equation

Algebra
Tutor: None Selected Time limit: 1 Day

log 3 + log(x − 6) = log x.
 
(a) First, we combine the logarithms to get the equivalent equation  = log x.
 

(b) Next, we write each side in exponential form to get the equivalent equation  = x.
 

(c) Now we find x = .
Apr 14th, 2015

a.    log(3*(x-6)) = log x

b.  3(x-6) =x

3x-18 =x

2x = 18

c.  x = 9  Answer

Apr 14th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 14th, 2015
...
Apr 14th, 2015
Mar 29th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer